2011
DOI: 10.48550/arxiv.1108.3819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On finding many solutions to S-unit equations by solving linear equations on average

Abstract: We give improved lower bounds for the number of solutions of some Sunit equations over the integers, by counting the solutions of some associated linear equations as the coefficients in those equations vary over sparse sets. This method is quite conceptually straightforward, although its successful implementation involves, amongst other things, a slightly subtle use of a large sieve inequality. We also present two other results about solving linear equations on average over their coefficients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…with all their prime factors lying in S. Konyagin and Soundararajan [11] showed that this special case too has exponentially many solutions for certain well chosen sets S. Namely, they showed that there are sets S for which the equation a + 1 = c has at least exp(s 1/16 ) solutions. This was subsequently improved by Harper [7] who showed the existence of sets S for which there are at least exp(s 1/6−ǫ ) solutions. In this paper we make further progress on this question, by showing that there are sets S with at least exp(s 1/4 / log s) solutions.…”
Section: Introductionmentioning
confidence: 98%
“…with all their prime factors lying in S. Konyagin and Soundararajan [11] showed that this special case too has exponentially many solutions for certain well chosen sets S. Namely, they showed that there are sets S for which the equation a + 1 = c has at least exp(s 1/16 ) solutions. This was subsequently improved by Harper [7] who showed the existence of sets S for which there are at least exp(s 1/6−ǫ ) solutions. In this paper we make further progress on this question, by showing that there are sets S with at least exp(s 1/4 / log s) solutions.…”
Section: Introductionmentioning
confidence: 98%